A sudden and unexpected death of a spouse and the severity of symptoms of complicated grief and Post-Traumatic Stress Disorder - Ludwikowska-Świeboda, Karolina (Kwartalnik Naukowy Fides et Ratio, 2022)
Introduction: The death of a spouse is one of the most stressful events in life. A better understanding of the factors leading to difficulties in adaptation to the situation of loss in widowed people seems to be important. The main goal of the presented study is to verify the role of the circumstances of the loss of a spouse (a sudden and unexpected death) with respect to severity of the symptoms of complicated grief and post-traumatic stress disorders. Method: Fifty five widowed people participated in the study (27 of them indicated that their spouse’s death occurred suddenly and unexpectedly, in the case of 28 people the loss had been anticipated). The time elapsed since death ranged from six months to 2.5 years. To measure the severity of complicated grief, the Complicated Grief Inventory by Prigerson et al. (in the Polish adaptation by Ludwikowska-Świeboda and Lachowska) was used. In order to assess the severity of symptoms of post-traumatic stress disorder (intrusion, avoidance and hyperarousal), the Impact of Event Scale — Revised by Weiss and Marmar (in the Polish adaptation by Juczyński and Ogińska-Bulik) was used. To determine the circumstances of the spouse’s death, a self-authored demographic data questionnaire was used. Results: As expected, the experience of a sudden and unexpected death is a significant predictor of the severity of complicated grief. Detailed analyses revealed that widowed people who experienced a sudden and unexpected death of their spouse are significantly more likely to be preoccupied with thinking about the deceased, experience shock and disbelief, and feel distanced from those who are important to them (compared to people who experienced an anticipated loss). They may also have a greater tendency to avoid stimuli reminding them of the deceased, experience more discomfort when recalling the deceased, and have difficulty trusting other people since their loss. A sudden and unexpected death is also a significant predictor of the severity of hyperarousal symptoms. Conclusions: Widowed people who view their spouse’s death as sudden and unexpected are at a greater risk of a disruption of the grief process.